Remoção de íons Pb²+ e Cu²+ em água de poço pelo zeólito natural clinoptilolita - Andrade, Eduardo Monteiro (2011)
This work assessed the removing capacity of Pb2+ and Cu2+ ions by clinoptilolite in aqueous solution and in water from a residential well in an industrial zone at the Centro Industrial do Subaé, Feira de Santana, Bahia. The chemical composition was evaluated by X-ray (XRF) and inductive coupled plasma (ICP). The results indicated that the composition of clinoptilolita Celta Brazil, with ratio Si / Al 5,92, is similar those reported in the literature as typical for this zeolite. Clinoptilolite characterized by X Ray diffraction presented 19% in the mordenite phase and 1,07 mmol/g as capacity of cationic exchange. The pseudo-second order kinetic model was used to assess adsorption rate in simple solution of metals. The adsorption data better matched Freundlich isotherm and the Pb2+ adsortion capacity was found as 5,33 mg/g while for the Cu2+ it was 2,22 mg/g. The adsorption kinetics revealed that the time of 120 minutes was sufficient to reach equilibrium. For the essays with well water, cupper was completely removed and only 48% of the Pb2+ was adsorbed, which suggests that in this real system the metal ratio charge/radii favored the adsorption of cupper on the clinoptilolite.